PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR ELEMEN GAMBAR TEKNIK - Fajar Ali Harefa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Over the past three academic years, students’ learning achievement in the Technical Drawing Element subject at SMK Negeri 14 Medan has remained relatively low. Data indicate that approximately half of the students have not been able to meet the established Minimum Mastery Criteria (MMC), which is set at 75. The previously implemented instructional model, Direct Instruction, was considered less effective as it was still teacher-centered. Based on these issues, this study was conducted to analyze the extent to which the implementation of the cooperative learning model, Student Teams Achievement Division (STAD), contributes to improving students’ learning outcomes. This research employed a quasi-experimental design involving Grade X students of the DPIB (Design Modeling and Building Information) program at SMK Negeri 14 Medan in the 2025/2026 academic year as the research sample. The experimental group received treatment through the implementation of the Student Teams Achievement Division (STAD) learning model, while the control group was taught using the Direct Instruction approach. The findings indicate that the implementation of the Student Teams Achievement Division (STAD) model has a significant effect on improving students’ learning outcomes. This is evidenced by the average score of the experimental class, which was 88.06, higher than that of the control class with an average of 61.94. Hypothesis testing using the t-test showed that t_calculated = 2.545 was greater than t_table = 1.670, leading to the acceptance of Ha, which means that the STAD model has a significant effect on the learning outcomes in the Technical Drawing Element subject for Grade X DPIB students at SMK Negeri 14 Medan. ABSTRAK Dalam kurun waktu tiga tahun ajaran terakhir, capaian belajar siswa pada mata pelajaran Elemen Gambar Teknik di SMK Negeri 14 Medan tergolong masih rendah. Data menunjukkan bahwa kurang lebih setengah dari jumlah siswa belum mampu memenuhi standar Kriteria Ketuntasan Minimal (KKM) yang ditetapkan, yaitu 75. Model pembelajaran yang digunakan sebelumnya, yaitu Direct Instruction, dinilai kurang efektif karena masih berpusat pada guruBerdasarkan permasalahan tersebut, penelitian ini dilakukan untuk menganalisis sejauh mana penerapan model pembelajaran kooperatif tipe Student Teams Achievement Division (STAD) berkontribusi terhadap peningkatan hasil belajar siswa. Penelitian ini dilaksanakan melalui desain quasi-eksperimen yang melibatkan siswa kelas X Program Keahlian DPIB SMK Negeri 14 Medan pada Tahun Ajaran 2025/2026 sebagai sampel penelitian. Perlakuan berupa penerapan model pembelajaran Student Teams Achievement Division (STAD) diberikan kepada kelompok eksperimen, sedangkan kelompok kontrol memperoleh pembelajaran dengan pendekatan Direct Instruction. Temuan penelitian mengindikasikan bahwa penerapan model Student Teams Achievement Division (STAD) berpengaruh secara signifikan terhadap peningkatan hasil belajar siswa. Hal tersebut terlihat dari perolehan rata-rata nilai kelas eksperimen sebesar 88,06, yang lebih tinggi dibandingkan kelas kontrol dengan rata-rata 61,94. Pengujian hipotesis menggunakan uji-t menunjukkan nilai thitung = 2,545 lebih besar dari ttabel = 1,670 sehingga Ha diterima, yang berarti model STAD berpengaruh signifikan terhadap hasil belajar Elemen Gambar Teknik siswa kelas X DPIB SMK Negeri 14 Medan.